Faktor-Faktor yang Mempengaruhi Konversi Lahan Perkebunan Cengkeh di Desa Tolong Kecamatan Lede Kabupaten Pulau Taliabu Provinsi Maluku Utara - La Hulu, Hamrin; Iswandi, R. Marsuki; Indarsyih, Yusna (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2017)
This study aims to determine the factors that affect the conversion of clove plantation land in Tolong Village, Lede District, Taliabu Island, North Maluku Province. The population of this study is all farmers who convert clove plantation (23 people) in Tolong Village, Lede District, Taliabu Regency, North Maluku Province. Sampling using purposive method (purposely) and samples were taken amounted to 23 people. The analytical method used is quantitative analysis with multiple linear regression analysis models. The results of this study indicate that the factors affecting the conversion of clove plantation in Tolong Village, Lede District, Taliabu Island, North Maluku Province, is the total price of clove trees sold, the production revenue and cost of.